Management of sphenoid lateral recess encephalocoeles - Govindaraju, Revadi; Tang, Ing Ping; Prepageran, Narayanan (Lippincott, Williams & Wilkins, 2018)
PURPOSE OF REVIEW: Sphenoid sinus lateral recess encephalocoeles (SSLRE) are rare occurrences and pose unique challenges due to limited surgical access for endoscopic endonasal repair and also the lack of consensus on optimal perioperative managements specifically in the spontaneous cases, which are also believed to be a variant of idiopathic intracranial hypertension (IIH). Endoscopic endonasal approaches have largely replaced the transcranial route and the techniques are continuously being refined to reduce the neurovascular morbidity and improve outcome. RECENT FINDINGS: Transpetrygoid is the most utilized approach with modifications suggested to limit bone removal, exposure and preservation of the neurovascular structures as dictated by the extent of the lateral recess. As more experience is gained, extended transphenoidal techniques were also successfully used for access. Lateral transorbital is a new approach to the lateral recess investigated in cadavers. IIH treatment is still controversial in the setting of SSLRE, but it appears rationale to evaluate, monitor and treat if necessary. SUMMARY: SSLRE management should be tailored to the specific anatomical variances and cause. Modifications of techniques have been described giving different options to access the lateral recess. Successful repair for spontaneous SSLRE may require treatment of IIH if present, but the long-term outcome is still unclear.